Employees’ Attitude Toward Women Managers in the UAE: Role of Socio-Demographic Factors - Nayeem, Mohammed Abdul (Journal of Comparative International Management, 2021)
This study aims to understand and examine the relationship between socio-demographic factors and the attitudes toward women managers in the context of the United Arab Emirates (UAE). This research paper is an exploratory research and we have taken into consideration a basic framework to understand the relationship that exists among different factors responsible for different perceptions and attitudes toward women managers. The literature review has focused on the various overarching perspectives of women managers and the attitudes formed by different societal actors. The paper draws mainly from the Social Learning Theory of Albert Bandura (1977). A sample of 213 employees was drawn to understand the relationship. The respondents were administered the well-established (Women as Managers Survey) WAMS questionnaire to get responses on various dimensions. Multivariate Regression Analysis using SPSS 26.0 version was applied to analyze the data.The findings of the study are parallel to previous works such that age, work experience, and educational level found support to the hypothesized relationship whereas gender and marital status did not. Limitations and future direction along with practical implications and recommendations are also given to draw suitable inferences.